Toward a literate future: pairing graphic novels and traditional texts in the high school classroom - Roberts, Nicolas J., author; Souder, Donna, advisor; Eskew, Doug, committee member; Taylor, Ted, committee member (Colorado State University. Libraries, 2012)
This thesis focuses on the need to incorporate visual literacy instruction in the secondary classroom. I begin by first exploring the need for a change in the instruction of literacy at the high school level; especially a change that emerges from those who are currently working in the high school classroom. I examine how visual literacy instruction can help to improve declining traditional literacy rates. The use of multimodal texts, such as graphic novels, has been proven to increase the ability of students to read traditional text-based works. I also look at the impact that the lack of visual literacy competency has on students when they leave the secondary setting. High schools are producing students who can consume visual culture, but they are unable to produce and critique that culture. This visual illiteracy places students at a disadvantage. They enter the culture with a lack of culture capital, and are missing the skills to attain more. In my argument, I suggest that one way to help improve the visual literacy skills of students is to incorporate graphic novels into the high school curriculum by pairing them with traditional texts. I offer suggestions for ways educators can make different pairing, based on the needs of their classrooms.
Keywords: visual literacy